2019
DOI: 10.1542/peds.2018-2656
|View full text |Cite
|
Sign up to set email alerts
|

Renal Replacement Therapy and Intermittent Catheterization Risk in Posterior Urethral Valves

Abstract: on behalf of the Pediatric Urology Midwest Alliance (PUMA) abstract OBJECTIVES: Posterior urethral valves predispose children to renal replacement therapy (RRT) and bladder dysfunction. Researchers of single-institutional series were unable to refine risk stratification because of rarity of the disease. We aimed to identify clinical variables associated with the risk of RRT and clean intermittent catheterization (CIC) in a large multicenter cohort study.METHODS: Children with posterior urethral valves born bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…Of the 59 children (9%) who underwent one or more catheter placements, 69% had them placed during the first year of life, and 83% were placed during the first 5 years of life. This distribution is similar to that observed by McLeod et al (21) in a recent multi-institutional analysis of children with posterior urethral valves. However, our overall rate of dialysis was lower, at 9% in our series versus 15% in theirs.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 59 children (9%) who underwent one or more catheter placements, 69% had them placed during the first year of life, and 83% were placed during the first 5 years of life. This distribution is similar to that observed by McLeod et al (21) in a recent multi-institutional analysis of children with posterior urethral valves. However, our overall rate of dialysis was lower, at 9% in our series versus 15% in theirs.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous observational retrospective study from our center in 2015, 1000 children with CKD were enrolled, the incidence of RRT was 7.7% (hemodialysis 3.6%, peritoneal dialysis 2.6%, and kidney transplantation 1.5%), and bladder dysfunction was the most frequent cause of obstructive uropathy (12.1%). 32 McLeod et al, 33 reported in a multicenter study, 274 children with PUV, who were treated before 90 days and were treated for a median of 6.3 years, 16% progressed to ESKD and required RRT by 10 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from multicenter cohorts from the United States of 274 [ 29 ] and 685 [ 5 ] patients have shed new light on the epidemiology of CKD and ESKD in children with PUV. At the ages of 1, 5 and 15 years, 7%, 12% and 20% of children needed KRT, respectively [ 5 , 29 ]. In a smaller study with 35 infants, after 10 years 50% progressed to CKD stages 2–4, and 15% needed KRT [ 30 ].…”
Section: Epidemiology Of Chronic Kidney Disease In Posterior Urethral...mentioning
confidence: 99%
“…The predictive value of serum creatinine has been identified as a useful parameter in several studies in patients with PUV. Different time points from first month [ 46 ] of life, in the first year of life [ 47 ], days, weeks or years after ablation [ 29 , 48 , 49 , 50 , 51 , 52 , 53 ], have been investigated. Some studies also focused on the creatinine velocity [ 51 , 54 ], which assesses the change in creatinine over time.…”
Section: Prognostic Factors For Chronic Kidney Disease Developmentmentioning
confidence: 99%
See 1 more Smart Citation